Medical applications with disentanglements: First MICCAI Workshop, MAD 2022, held in Conjunction with MICCAI 2022, Singapore, September 22, 2022, proceedings - Fragemann, Jana; Li, Jianning; Liu, Xiao; Tsaftaris, Sotirios A.; Egger, Jan; Kleesiek, Jens Philipp (Lecture Notes in Computer Science, 2023)
Applying Disentanglement in the Medical Domain: An Introduction -- HSIC-InfoGAN: Learning Unsupervised Disentangled Representations by Maximising Approximated Mutual Information -- Implicit Embeddings via GAN Inversion for High Resolution Chest Radiographs -- Disentangled Representation Learning for Privacy-Preserving Case-Based Explanations -- Instance-Specific Augmentation of Brain MRIs with Variational Autoencoder -- Low-rank and Sparse Metamorphic Autoencoders for Unsupervised Pathology Disentanglement -- Training β-VAE by Aggregating a Learned Gaussian Posterior with a Decoupled Decoder -- Disentangling Factors of Morpholigical Variation in an Invertible Brain Aging Model -- A study of representational properties of unsupervised anomaly detection in brain MRI.